Golden Aging : Prospects for Healthy, Active, and Prosperous Aging in Europe and Central Asia - Bussolo, Maurizio; Koettl, Johannes; Sinnott, Emily (Washington, DC: World Bank, 2015)
Compared to other regions, Europe and Central Asia are by far the oldest. Moreover, population aging is set to accelerate further over the coming decades as large segments turn old. Additionally, some countries such as Russia and certain Eastern European countries are facing a shrinkage of their population. Against this backdrop, this report investigates what stands in the way of societies reaping the full benefits of increased longevity—that is, longer lives and potentially prolonged payoffs from human capital—and what can help to mitigate the possible negative impacts of a smaller and older workforce.